OCA Oracle database SQL exam guide : (exam 1Z0-071) - O'Hearn, Steve (Oracle Press, 2017)
A fully updated, integrated self-study system for the Oracle Database SQL Exam This thoroughly revised Oracle Press guide offers 100% coverage of all objectives on the latest version of the Oracle Database SQL Exam. Ideal both as a study guide and on-the-job reference, OCA Oracle Database SQL Exam Guide (Exam 1Z0-071) features detailed explanations, examples, practice questions, and chapter summaries. "Certification Objectives," "Exam Watch," and "On the Job" sections reinforce salient points throughout. You will gain access to two complete practice exams that match the tone, tenor, and format of the live test. Get complete coverage every topic on Exam 1Z0-071, including: DDL and SQL SELECT statements Manipulating, restricting, and sorting data Single-row and group functions Displaying data from multiple tables Subqueries Schema objects Set operators Grouping related data Report creation Data dictionary views Large data sets Hierarchical retrieval Regular expression support User access control The electronic includes: Two full practice exams Detailed answers and explanations